The nature of business information services provision in public libraries in Malaysia: a case study / Masuri Ismail - Ismail, Masuri (2017)
Business information consisting of published data, facts and statistics are important for decision-making in business organizations, private or public, as well as in the government sector. The public libraries (PL) that offers Business Information Services (BIS) can play an important role in sourcing timely marketing information, financial, bank and company information, laws and tax regulations, economic, commercial and trade information, as well as factual information about the environment in which businesses and other organizations operate. The service sector was identified as the country's new growth engine and has been featured in various development programs including New Economic Model and the 10th Malaysia Plan. The objectives of this study are to: (i) Explore current practices in public state libraries with Business Information Services (BIS) and (ii) Identify the basic Business Information Services (BIS) elements in public libraries in Malaysia. This study sought to discover the nature of business information services offered in the public business library. Thirteen (13) libraries in Malaysia excluding the federal territories had been selected for a preliminary study. Three state libraries claimed and were found to offer BIS. These three libraries were then selected for the case studies. Data was collected through a review of related literature; telephone interview; observation; face-to-face interviews with the person-in-charge of the business information service; and supported by the document analysis. The researcher found that, there are fourteen (14) elements that are important in the provision of BIS in PL in Malaysia. They are: Reference Services; Outreach Efforts; Web Page; Marketing; Information, Communication and Technology (ICT); Collaboration and Partnerships; Resources; Budget; Business Librarian; User Education; Physical Space; Research Services; Information Repackaging; and Document Dissemination Services. This case study focused on the public business library in Malaysia. Further research can be expanded to include other types of business libraries such as corporate business libraries and academic business libraries. Since this conceptual framework is applicable to any type of business libraries in Malaysia, the 14 elements can be used to study the nature of academic and corporate business libraries in Malaysia and further measure the implementation of BIS in these libraries. Each of the elements can be studied separately by different researchers to further an in-depth study of each of the 14 elements. Other researchers also can studied about the effectiveness of BIS in PL in Malaysia using other methods of study.